Diseño e implementación de un sistema de control de temperatura y riego automatizado para una máquina tipo Sellopol en la empresa Plásticos Vaqueros del Huila (2022)
Currently, in the department of Huila, there are 10 companies dedicated to the manufacture of plastic bags, including Plasticos Vaqueros, a micro 20 years of experience in the sector. However, they require one or two permanent and tcompany with more than rained operators, who are in charge of processes such as production counting, temperature adjustment for sealing the bags by manipulating a cable that is connected to a terminal increasing or decreasing the power received by the resistance and maintaining a constant humidity for the conveyor belt by means of irrigation through a gallon and thus avoid adherence of the bag on the belt. These processes were optimized with the design and implementation of an automated system that by means of a PID control maint ains the sealing temperature at 180 and 250 °C optimum operating point for sealing, as well as the inclusion of an anti which eliminates the manual work of the operator.